2017
DOI: 10.1111/1758-2229.12503
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of K+ uptake permease (Kup) for resistance to sucrose‐induced stress in Gluconacetobacter diazotrophicus PAl 5

Abstract: Microorganisms are constantly challenged by stressful conditions, such as sugar-rich environments. Such environments can cause an imbalance of biochemical activities and compromise cell multiplication. Gluconacetobacter diazotrophicus PAl 5 is among the most sugar-tolerant bacteria, capable of growing in the presence of up to 876 mM sucrose. However, the molecular mechanisms involved in its response to high sucrose remain unknown. The present work aimed to identify sucrose-induced stress resistance genes in G.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…4C and D , Tables S1 and S2 ). Kup has been described in different bacteria as the major K + transporter, essential in hyperosmotic conditions using sucrose as osmotic stressor (38, 39). Moreover, in a previous study, we found that the TCS ChvGI in C. crescentus positively controls the expression of kup in hyperosmotic conditions (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C and D , Tables S1 and S2 ). Kup has been described in different bacteria as the major K + transporter, essential in hyperosmotic conditions using sucrose as osmotic stressor (38, 39). Moreover, in a previous study, we found that the TCS ChvGI in C. crescentus positively controls the expression of kup in hyperosmotic conditions (37).…”
Section: Resultsmentioning
confidence: 99%
“…4B, Tables S1 and S2). Kup has been described in different bacteria as the major K + transporter, essential in hyperosmotic conditions using sucrose as osmotic stressor (de Oliveira et al, 2017, Trchounian & Kobayashi, 1999.…”
Section: Kup Becomes Dispensable In Limiting K + Conditionsmentioning
confidence: 99%
“…diazotrophicus is one of the relatively few bacteria capable of being cultured at very high sucrose concentrations (876 mM sucrose [28]; 30% [29]) and can tolerate a water activity level of 0.892 aw [26]. This is perhaps not surprising given its host plant, sugarcane and other high sucrose content host plants from which it has been isolated ( Table 1), but for G. diazotrophicus to tolerate sucrose-induced stress, it has to have the mechanisms with which to cope.…”
Section: G Diazotrophicus: An "Extra-ordinary Endophyte"mentioning
confidence: 99%